A research study on forgiveness, a manifestation of the glory of God and its importance and virtue: معافی شانِ ربوبیت کا مظہر اور اس کی اہمیت و فضیلت کا تحقیقی مطالعہ - Islam, Muhammad Umar (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
This research paper comprises a, Forgiveness and clemency are the perfection of human life, bringing breadth and beauty to a person’s personality. This is the path of gentleness and mercy that keeps one safe from all kinds of harm and protects one from all kinds of immorality and savagery. This is also a cause of a person’s rise and fall to some extent. Throughout history, every era has given great and powerful nations some respite from oppression, but then they were destroyed in such a way that every era remembered them with humiliation. However, when forgiveness and clemency were found in a nation, they were never deprived of honor and dignity in any part of history. In human history, there are many individuals who have explicitly dedicated their lives to the social and religious reform of their loved ones. Despite such great responsibility and office, if someone else is hurt, they forgive them with their great creation, "forgiveness and clemency," and treat them with even more respect and honor than before. This quality softens even the hardest of hearts in every field. Human history is full of conflicts and disagreements, and it is human nature to have differences arise somewhere. As Muslims, if we analyze the history of Islam, especially the era of the Prophet (peace be upon him), we will see that there were disagreements and differences among the Companions (may Allah be pleased with them) and the righteous predecessors. However, they never exceeded the bounds of Allah’s command, and they always prioritized forgiveness and clemency. In reality, the lack of awareness of the virtues and benefits of forgiveness and clemency in Islam is the cause of our downfall. Mercy has no limits because it is an attribute of the Merciful, who has no limits, and nothing is beyond His mercy, just as nothing is beyond His power and wisdom. We are all servants of Allah, and Allah demands from us that we show mercy to His creation so that He may show mercy to us. When we are adorned with this excellent quality, we will undoubtedly be deserving of Allah’s mercy in this world and the hereafter. This aspect of forgiveness and clemency is so important that it has been made the foundation of good social behavior. In its implementation, even small lies are allowed for the sake of reconciliation and compromise, so that differences can be resolved and love can grow between people. Rights and responsibilities are always changing, and forgiveness is the key to maintaining relationships. However, it is very difficult to be patient in the face of injustice, and one must also bear losses. But the real loss is to deviate from Allah’s command of patience and forgiveness. Every relationship, whether between parents and children, spouses, siblings, or rulers and subjects, depends on mutual forgiveness. Socially, intolerance leads to strife, discord, and extremism, which have negative effects not only on the parties involved but also on others associated with them. Eventually, this intolerance takes the form of prejudice and becomes a source of racial hatred.